Reliability of Progress Curves in Airframe Production - Alchian, Armen (Econometrica, 1963)
This report presents a statistical study of the reliability of a given function for certain types of estimates in the aircraft industry and Air Force. It is indisputable that lower direct labor costs occur as the number of items produced increases. Questions can be raised, however, about the specifics of planning, estimating, and forecasting using this function.